Funtional characterization of sweet potato acetylated starch and use it in formulation of fruit puddings. - Anchundia Lucas, Miguel Â´Íngel (SATHIRI, 2019)
In order to diversify the use of native and acetylated starch sweet potato in food formulation and increase the use of these tropical crops were characterized the polysaccharides functional properties through the determination of swelling power, solubility in water, water absorption capacity and rheological properties by the official methodology. Puddings were formulated using sweet potato native starch, acetylated and a mixture of both, as well as, sugar, salt, milk and fruit pulp. In the obtained dessert sensory, physicochemical and microbiologically were evaluated. There were statistically significant differences (p≤0.05) by acetylation, there where increase in water absorption, swelling power and solubility index. In acetylated starch cooked pastas, the rheological parameters, initial temperature of starch gelatinization and setback viscosity decreased slightly, maximum viscosity and breakdown stability index were increased. Formulations 3 and 8 were selected since obtained product had desired sensory characteristics. The prepared puddings with acetylated starch showed statistically significant differences (p≤0.05) in the humidity, pH, consistency and global acceptance in sensory analysis. The obtained results showed that the use of a native and acetylated starch mixture was suitable for the puddings preparation since they presented good physical-chemical and microbiological quality and a good sensory acceptance.